The green seaweed Ulva: a model system to study morphogenesis - Wichard, Thomas; Charrier, Bénédicte; Mineur, Frédéric; Bothwell, John H.; Clerck, Olivier De; Coates, Juliet C. (Frontiers in Plant Science, 2015)
Green macroalgae, mostly represented by the Ulvophyceae, the main multicellular branch of the Chlorophyceae, constitute important primary producers of marine and brackish coastal ecosystems. Ulva or sea lettuce species are some of the most abundant representatives, being ubiquitous in coastal benthic communities around the world. Nonetheless the genus also remains largely understudied. This review highlights Ulva as an exciting novel model organism for studies of algal growth, development and morphogenesis as well as mutualistic interactions. The key reasons that Ulva is potentially such a good model system are: (i) patterns of Ulva development can drive ecologically important events, such as the increasing number of green tides observed worldwide as a result of eutrophication of coastal waters, (ii) Ulva growth is symbiotic, with proper development requiring close association with bacterial epiphytes, (iii) Ulva is extremely developmentally plastic, which can shed light on the transition from simple to complex multicellularity and (iv) Ulva will provide additional information about the evolution of the green lineage.